Development of 2-D augmented reality integrated physics e-book to improve students' problem-solving skills - Nugraheni, Veronika Yeni Setyo Tri; Mundilarto, Mundilarto (Momentum: Physics Education Journal, 2022)
This study aims to produce an augmented reality integrated e-book that is feasible to improve the problem-solving skills of 11th graders; identify the improvement of 11th graders problem-solving skills after using the augmented reality integrated e-book. Problem-solving as a way of obtaining solutions to difficulties is divided into four indicators, which are: understanding the problem, making plans, implementing plans, and reviewing solutions. Data collection techniques consist of tests, questionnaires, observations, and documentation using instruments that support the Research and Development (R&D) technique with a 4D model. Research subjects were selected by simple random sampling with 34 students of 11th graders. In this study, questionnaires were used for validation, observations were made to determine the condition of students, and documentation was used as evidence in conducting research. The data were analyzed quantitatively based on the results of the validation and analysis of pretest and posttest items. The results showed that the augmented reality integrated e-book is feasible to use based on the results of validation using the average value conducted by a very high category validator, and the validation value obtained is 3.79. The improvement of problem-solving skills was analyzed using Normalized Gain, and the improvement of problem-solving skills got a score of 0.8 in the high category.